Analisis Pengukuran Tegangan Pada Struktur Pelat Berbasis Microcontroller Arduino - Ramli Ali Safrudin; Feblil Huda; Sapdo Utomo (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Stress can be measured using a strain gauge sensor. Strain gauge will experience change in resistance when the objects are tied with strained. The magnitude of the difference in resistance on the strain gauge is proportional to the strain on the object. In this study, using a device for strain gauge signal reading from materials that are cheap and easily found in the Indonesian market, including Arduino (as data acquisition) and INA 125P (as signal amplifiers). Stress measurements performed on Aluminum plates use the bending load like the cantilever beam with dimensions of 150 mm long, 50 mm wide, 2 mm thick. The measurement results obtained have the biggest difference with the theoretical calculation method which is 5,32%, while when compared with the simulation method the biggest difference is 8,03%.Keyword : Strain gauge, INA 125P, cantilever beam, bending load.